Value of intraoperative post-conisation human papillomavirus testing in predicting residual or recurrence after treatment with a loop electrosurgical excision procedure in women with HR-HPV positive and cervical high-grade squamous intraepithelial lesion - Weiting Xia; Xinyue Dai; Yan Hu; Simeng Yang; Chen Chen; Xiaolin Li (BMC Cancer)
Abstract Objective To evaluate the feasibility of intraoperative human papillomavirus (IOP-HPV) testing for the prediction of postoperative treatment failure in patients with high-grade squamous intraepithelial lesion (HSIL) undergoing loop electrosurgical excisional procedure (LEEP). Methods A total of 114 women diagnosed with HSIL by biopsy and/or endocervical curettage who underwent LEEP were included in a prospective cohort study. IOP-HPV testing was performed immediately after the procedure. Patients were followed up for 24 months. Logistic regression was used to analyse the factors influencing the residual or recurrent lesions. Further stratified analyses were performed to investigate the differences in prognosis of IOP-HPV positivity in patients of different age and menopausal status. Results 1. Of the 114 patients, 6 (5.26%) were pathologically upgraded to cervical cancer, and 21 (18.42%) were lost to follow-up. Recurrence or residual HSIL lesions occurred in 9.20% (8/87) of cases. Of the 8 women who developed post-treatment HSIL, 7 (26.92%) were positive for IOP-HPV, and only 1 (1.64%) was negative for IOP-HPV (< 0.01). 2. Transformation zones of type 2 (P = 0.0306) or type 3 (P = 0.0446), diagnosed as LSIL/negative by cervical biopsy (P = 0.0396), margin involvement (P = 0.0233), positive endocervical curettage after conisation (P = 0.0028), intraoperative HPV-positive (P < 0.01), cytological abnormalities (P = 0.0038), DNA ploidy positivity (P = 0.0172), postoperative HPV (P < 0.01) and DNA ploidy (P = 0.0078) positivity at 6 months were associated with higher risk of residual or recurrent lesions.  3. The results of the multivariate regression analysis showed that IOP-HPV positivity was the independent risk factor for residual or recurrent lesions (OR=10.69 , 95% CI:3.41, 33.51, P<0.01). IOP-HPV positivity was strongly associated with the occurrence of residual/recurrent LSIL (OR=6.42 , 95% CI:1.74, 23.70, P=0.0053) and HSIL (OR=32.08 , 95% CI:3.60, 285.64, P=0.0019). 4. Stratified analyses showed that IOP-HPV positive in patients younger than 50 years or premenopausal patients was associated with a significantly higher risk of recurrence or residual lesions (p<0.05). Conclusions IOP-HPV positivity is an independent risk factor for residual or recurrent HSIL lesions. In addition, IOP-HPV positivity was more associated with residual or recurrent lesions in those younger than 50 years or premenopausal. IOP-HPV testing may be of critical clinical value in providing the early and accurate prediction of residual or recurrent lesions.